The Supply and Control of Money: A Note - Anderson, Benjamin M. (Quarterly Journal of Economics, 1935)
Journal Article A Note Get access Benjamin M. Anderson, Jr. Benjamin M. Anderson, Jr. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 49, Issue 4, August 1935, Page 705, https://doi.org/10.2307/1885407 Published: 01 August 1935